Smart polymer nanocomposites: A review - W. S. Chow; Z. A. Mohd Ishak (eXPRESS Polymer Letters)
The development of smart polymer nanocomposites (SPN) has been an area of high scientific and industrial interest in recent years, due to fantastic improvements achieved in these materials. SPN found potential applications in shape memory, self-healing, self-sensing, self-heating, self-cleaning, and energy harvesting. This mini-review highlights the current research and development on SPN, specifically on shape memory polymer (SMP) and self-healing polymer (SHP) nanocomposites. The processing techniques for SPN nanocomposites, for example, polymerization, melt-compounding, solution mixing, electrospinning, and thermoset-curing are discussed. Some of the potential strategies to modify the properties of SMP and SHP nanocomposites are highlighted. The future perspective and recommended works for the SPN nanocomposites are shared in this mini-review.